The Interaction of Sound and Meaning in Qur’ānic Words: A Tonal Approach - Ömer, Faruk Es (Department of Religious Studies, 2020)
Muslims believe that the Qur’ān is the Speech of God with all its sound and sense. The association of the sound with Divine speech triggers the anticipation that the sound and meaning in the Qur’ān have to be intertwined. This expectation is heightened since according to a vast majority of Muslim scholars, the most powerful facet of the miraculousness and inimitability of the Qur’ān (iʻjāz) is the aesthetic excellence of its eloquence (balāḡah) and articulacy (fasāḥah). And intriguingly, in parallel to the intricate relationship of sound and meaning, the attempts of Muslim rhetoricians to identify the source and enchantment of Qur’ānic eloquence have been developed around, and challenged by the distinction of meaning (maʻnā) and expression (lafẓ), which has long continued to be a most elusive problem. In this connection, there are several signi2icant contemporary studies such as of Michael Sells and Kristina Nelson, which develop the traditional analysis further by charting the aural structures of Qur’ānic passages on the basis of the parallelisms and divergencies of syntactic, phonological, and rhythmic features, which are interpreted through the musical tonal dynamics. And the ways in which the aural structures become distinct of each other are read in parallel with the generation of Qur’ānic meanings. These studies construct a fertile formal framework for sound-meaning interaction, without, however, focusing upon how they are instantaneously correlated. In this regard, we encounter a unique work of Sayyid Quṭb, Artistic Imagery in the Qur’ān, in which Quṭb propounds that the fundamental principle and the most valuable stylistic quality of Qur’ānic language is artistic imagery (taswīr), through which the meanings are depicted and portrayed in a vividly evocative way kindling the feeling that the Qur’ānic expression is “alive”. As a crucial dimension of taswīr, Quṭb suggests that the tonal and articulatory features of the letters depict the meanings of the words, and the ways in which they are sequenced generate unique styles of inner musicality that portray the moods and atmospheres of the passages. However, in his cursory discussion, Quṭb does not explain what these tonal qualities are, and how they work. This dissertation develops the concept of taswīr around the concept of tonality and investigates the sound-meaning relationship by meticulously dissecting the articulatory dynamics of the letters and their expressive and evocative qualities.